Aspectual Verbs: a study of cease and continue - Geneviève Girard-Gillet (Anglophonia)
Two aspectual verbs, “cease” and “continue” do not conform to the usual opposition that exists between an infinitival complement and a gerund clause, and thus cannot be compared with “stop” or “carry on”. Unlike what happens with “stop”, the infinitive after “cease” does not express a goal, but, on the contrary, the cessation of the process that was developing. The infinitive after “continue” does not mean that a process was resumed after its cessation, but that there was no cessation at all. These differences call for an analysis of the parameters that construe the diverging interpretations. The to+V and V-ing opposition does not play the same role it does with other verbs. Drawing on examples in context, we will show that the interpretation depends on the semantic features of the main verb, which is more complex than usually acknowledged, on the role played by the referent of the subject and on the way the speaker conceptualizes the event. This paper builds and enlarges on earlier works, by taking into account what type of causation is implied.